An antimicrobial effect associated with rabbit primary aqueous humour. Issue 2 (February 1994) - Diamond, J P; Leeming, J P; Smart, A D; Duffus, P; Hedges, A J; Easty, D L
Abstract : Viability curves were recorded for a variety of bacteria suspended in rabbit primary aqueous humour. Controls included neat rabbit serum, dilute rabbit serum (1/50), dilute heat treated fetal bovine serum (1/50), and balanced salt solution. Rabbit aqueous humour was bactericidal in vitro for Staphylococcus aureus and Pseudomonas aeruginosa. Micrococcus spp, Streptococcus pneumoniae and Escherichia coli were not affected. The factor mediating the bactericidal effect survives filtration (0.2 micron porosity) and freezing in liquid nitrogen (-196 degrees C) but is labile when stored in air at temperatures of 4 degrees C, 25 degrees C, and 37 degrees C for 1 hour. The bactericidal effect was stable when aqueous humour was stored in an atmosphere of 5% CO2 at 37 degrees C for 3 hours. The antibacterial component in rabbit aqueous humour has yet to be identified.